Case report: Pallidal deep brain stimulation for treatment of tardive dystonia/dyskinesia secondary to chronic metoclopramide medication - Nagel, Johanna M.; Ghika, Joseph; Runge, Joachim; Wolf, Marc E.; Krauss, Joachim K. (Frontiers in Neurology, 2023)
Objectives: Tardive dystonia and dyskinesia (TDD) occurs as a side effect of anti-dopaminergic drugs, including metoclopramide, and is often refractory to medication. While pallidal deep brain stimulation (DBS) has become an accepted treatment for TDD secondary to neuroleptic medication, there is very little knowledge about its effects on metoclopramide-induced TDD. Methods: We present the case of a woman with metoclopramide-induced TDD, whose symptoms were initially misjudged as “functional”. After eight years of ineffective medical treatments, she received bilateral implantation of quadripolar electrodes into the posteroventral lateral globus pallidus internus (GPi). Results: GPi DBS led to significant symptom reduction (Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) motor score 24/44 at admission, 7/44 at discharge. Chronic stimulation led to full recovery from TDD symptoms nine years after surgery. The BFMDRS motor score decreased to 0.5 (improvement by 98%). Discussion: Pallidal DBS may result in sustained improvement of TDD secondary to chronic metoclopramide intake on long-term.